Analisis Biaya Satuan Kateterisasi Koroner Menggunakan Metode Penetapan Biaya Berbasis Aktivitas dalam Layanan Jantung Terpadu di Rumah Sakit Umum Islam Klaten - Suwanto Suswanto (Jurnal Admmirasi, 2020)
The application of universal coverage by the Social Security Organizing Agency that uses payments with the INA-CBG's package tariff system (Permenkes No.27, 2014). So that in the management of diseases and medical measures needs to control quality and costs. One of the medical procedures that require high cost and investment is coronary artery catheterization. Klaten Islamic Hospital is a type B hospital that establishes cardiac services as superior service, so an accurate unit cost calculation is needed regarding the cost of coronary artery catheterization procedures. This descriptive qualitative study was conducted in October - November 2019. Analysis of the unit cost of coronary artery catheterization using annual data based on the 2018 activity report using the ABC-Baker method by detailing direct costs, direct and indirect overhead costs, and unit costs for each activity. Calculation of unit cost of coronary artery catheterization in integrated cardiac services at the Klaten Islamic General Hospital using Activity Based Costing methods including Percutaneous coronary intervention (PCI) is IDR.36,251,719 which is composed of direct cost IDR.35.654.570 direct overhead cost IDR.463.757 and indirect overhead cost IDR.133.392 and for Coronary Angiography (CAG) procedure is IDR.13.462.326 which is composed of direct cost IDR.13.059.878 direct overhead cost IDR. 318.954 and indirect overhead cost IDR. 83.494. Conclusion: There is a negative difference between the unit cost of the ABC-Baker method and the INA-CBG's rate on angiographic measures of (IDR. 5,852,726). And a positive difference was found between unit cost of ABC-Baker method and the INA-CBG's rate on the PCI procedure of IDR.5, 338,781.